In the book modal logic for open minds by johan van benthem there is on page 161 a statement that the sentence $\langle (R\lor S)* \rangle \phi$ is equivalent to the sentence $\langle (R* ; S*)* \rangle \phi$
(* means iteration and ; means composition here)
So:
$\langle (R\lor S)* \rangle \phi \equiv \langle (R* ; S*)* \rangle \phi$
Why is this equivalent to each other?
(* means iteration and ; means composition here)
So:
$\langle (R\lor S)* \rangle \phi \equiv \langle (R* ; S*)* \rangle \phi$
Why is this equivalent to each other?